Identification of Cerebral Metal Ion Imbalance in the Brain of Aging Octodon degus - Braidy, Nady; Poljak, Anne; Marjo, Chris; Rutlidge, Helen; Rich, Anne; Jugder, Bat-Erdene; Jayasena, Tharusha; Inestrosa, Nibaldo C.; Sachdev, Perminder S. (Frontiers in Aging Neuroscience, 2017)
The accumulation of redox-active transition metals in the brain and metal dyshomeostasis are thought to be associated with the aetiology and pathogenesis of several neurodegenerative diseases, and Alzheimer’s disease (AD) in particular. As well, distinct biometal imaging and role of metal uptake transporters are central to understanding AD pathogenesis and ageing but remain elusive, due inappropriate detection methods. We therefore hypothesised that O.degus develop neuropathological abnormalities in the distribution of redox active biometals, and this effect may be due to alterations in the expression of lysosomal protein, major Fe/Cu transporters, and selected Zn transporters (ZnTs and ZIPs). Herein, we report the distribution profile of biometals in the aged brain of the endemic Chilean rodent Octodon degus (O. degus) – a natural model to investigate the role of metals on the onset and progression of AD. Using laser ablation inductively coupled plasma mass spectrometry (LA-ICPMS), our quantitative images of biometals (Fe, Ca, Zn, Cu, and Al) appear significantly elevated in the aged O.degus and show an age-dependent rise. The metals Fe, Ca, Zn, and Cu were specifically enriched in the cortex and hippocampus, which are the regions where amyloid plaques, tau phosphorylation and glial alterations are most commonly reported, whilst Al was enriched in the hippocampus alone. Using whole brain extracts, age-related deregulation of metal trafficking pathways was also observed in O.degus. More specifically, we observed impaired lysosomal function, demonstrated by increased Cathepsin D protein expression. An age-related reduction in the expression of subunit B2 of V-ATPase, and significant increases in amyloid beta 42 (Aβ42), and the metal transporter ATP13a2 were also observed. Although the protein expression levels of the zinc transporters, ZnT(1,3,4,6, and 7), and ZIP7,8 and ZIP14 increased in the brain of aged O.degus, ZnT10, decreased. Although no significant age-related change was observed for the major iron/copper regulator IRP2, we did find a significant increase in the expression of DMT1, a major transporter of divalent metal species, 5’-aminolevulinate synthase 2 (ALAS2), and the proto-oncogene, FOS. Collectively, our data indicate that transition metals may be enriched with age in the brains of O. degus, and metal dyshomeostasis in specific brain